Detection and molecular characterization of zoonotic poxviruses circulating in the amazon region of Colombia, 2014 (2017)
During 2014, cutaneous lesions were reported in dairy cattle and farmworkers in the Amazon Region of western Colombia. Samples from 6 patients were analyzed by serologic and PCR testing, and results demonstrated the presence of vaccinia virus and pseudocowpox virus. These findings highlight the need for increased poxvirus surveillance in Colombia. © 2017, Centers for Disease Control and Prevention (CDC). All Rights Reserved.